Nutritional status, immunonutrition, and gut microbiome: a coming of age for immunotherapy? - Mattavelli, Elisa; Agustoni, Francesco; Tartara, Alice; De Simeis, Francesca; Perrone, Lorenzo; Caccialanza, Riccardo; Pedrazzoli, Paolo; Da Prat, Valentina (Frontiers in Immunology, 2025)
In the last decades, immunotherapy has revolutionized cancer treatment. Despite its success, a significant number of patients fail to respond, and the underlying causes of ineffectiveness remain poorly understood. Factors such as nutritional status and body composition are emerging as key predictors of immunotherapy outcomes. In particular, poor nutritional status, sarcopenia, and low skeletal muscle mass are associated with poorer survival and immunotherapy response in several cancers. Conversely, certain parameters of body composition, such as adiposity, may have beneficial effects on immunotherapy efficacy. Nutritional status and body composition can be targeted through tailored nutritional support, making it a potential strategy to improve immunotherapy outcomes. Specific nutrients and modulation of the gut microbiota may further enhance immune functions, offering promising avenues for clinical improvement. Despite the promising potential of tailored nutritional support, clinical evidence remains limited, and further research is needed to establish optimal strategies to optimize immunotherapy response and effectiveness.